The Phenotypic and the Genetic Response to the Extreme High Temperature Provides New Insight Into Thermal Tolerance for the Pacific Oyster Crassostrea gigas - Ding, Fangfang; Li, Ao; Cong, Rihao; Wang, Xinxing; Wang, Wei; Que, Huayong; Zhang, Guofan; Li, Li (Frontiers in Marine Science, 2020)
Investigating responses of organisms to stressful or new environments with selection pressure is one of the crucial problems in evolutionary biology, and it is of importance to understand the mechanism undying thermal tolerance under the context of the climate change. The Pacific oyster, Crassostrea gigas, inhabiting the environment with high variation in temperature, is a worldwide aquaculture species. However, summer mortality relevant to the high temperature is one of the problems challenging the oyster industry. We initialized an artificial selective breeding program to select for the thermal tolerance of oysters in an attempt to increase the summer survival rates since 2017. And the phenotypic and the genotypic response to extreme high temperature were investigated based on the comparison of the F1 progeny of the selected and natural populations in growth, physiology, mortality rate post heat stress, genetic structure, and gene expression. The parameter of growth showed no significant change between the selected and natural populations for the six-month-old oysters. The selected population exhibited a higher survival rate after exposure to heat stress in the laboratory, which is in line with field studies. Further, the respiration rate of the selected population increased at 38 ℃, while it increased at 35 ℃ in the natural population. And metabolism-related enzymes showed higher activity levels in the selected population. Furthermore, phylogenetic analysis, population structure, and principal component analysis (PCA) suggested that the selected and natural populations exhibited genetic divergence, with eight genes (IF4A2, IF6, EIF3A, MANBA, DDX43, RECS, CAT2, and BAG4) in the selected regions showing differential expression patterns in response to heat stress in the two populations. This study suggests that artificial selection has a significant effect on phenotype and genome structure for the oyster, our study provides an alternative way to reveal the mechanism underlying thermotolerance that plays an important role to predict the potential adaptation to the climate change.